Project network management: risks and contributors from the viewpoint of contractors and sub-contractors - Hwang, Bon Gang; Ng, Han Boey (Technological and Economic Development of Economy, 2016)
Over the years, the network of construction project participants has expanded immensely. Clients have more stringent requirements due to increasing project complexity, difficulties with interaction and coordination, and uncertainties among various stakeholders. Emergent issues can bring many uncertain risks to the project execution process and yet the body of knowledge in this area, as applied to the Singapore construction environment, is insufficient. Therefore, the main objective of this study is to identify critical network risks extant in the industry in order to attain a better understanding of the attitudes of stakeholders towards network risk management. Thirtythree construction companies participated in a survey developed for this study and the analysis of the responses identified ten top critical network risks and the stakeholders who most contribute to these risks. The findings from this study will help the industry to promote a healthy working relationship among stakeholders, and will further facilitate collaboration within the project network.First published online: 18 Sep 2015